2000
DOI: 10.1016/s0735-1097(99)00494-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the acute hemodynamic effects of inhaled nitric oxide and aerosolized iloprost in primary pulmonary hypertension

Abstract: During acute drug testing, aerosolized iloprost was more potent than inhaled NO as a pulmonary vasodilator in PPH at the doses used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
172
1
19

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(208 citation statements)
references
References 24 publications
16
172
1
19
Order By: Relevance
“…2 As an alternative, inhaled nitric oxide possesses pulmonary selectivity, but it is less potent than prostacyclin in the pulmonary vasculature. 3,4 Moreover, an interruption in the inhalation of continuous nitric oxide may cause rebound pulmonary hypertension. 5,6 Designed to combine the beneficial effects of prostacyclin with those of an inhalational application, aerosolized prostacyclin was found to be a potent pulmonary vasodilator in patients with acute respiratory failure, exerting preferential vasodilatation in well-ventilated lung regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As an alternative, inhaled nitric oxide possesses pulmonary selectivity, but it is less potent than prostacyclin in the pulmonary vasculature. 3,4 Moreover, an interruption in the inhalation of continuous nitric oxide may cause rebound pulmonary hypertension. 5,6 Designed to combine the beneficial effects of prostacyclin with those of an inhalational application, aerosolized prostacyclin was found to be a potent pulmonary vasodilator in patients with acute respiratory failure, exerting preferential vasodilatation in well-ventilated lung regions.…”
Section: Resultsmentioning
confidence: 99%
“…12 When administered during a short aerosolization ma-neuver to patients with pulmonary hypertension, its pulmonary vasodilative potency was similar to that of prostacyclin, but its effects lasted for 30 to 90 minutes, as compared with 15 minutes. 4,11,[13][14][15] Several open-label, uncontrolled studies of patients with severe pulmonary hypertension suggested that longterm use of aerosolized iloprost results in substantial clinical improvement. 11,13,[16][17][18][19][20] Our objective in this trial was to evaluate the effects of inhaled iloprost using a rigorous end point of clinical efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Although it may be possible to administer iloprost intravenously, the drug has gained attention recently for delivery by inhalation. In idiopathic PAH, short-term inhalation of iloprost resulted in greater pulmonary vasodilatation than did nitric oxide (65). For long-term use, the relatively short duration of action of inhaled iloprost necessitates 6 to 9 inhalations per day (66,67).…”
Section: Prostanoidsmentioning
confidence: 99%
“…Bolus doses between 15 and 30 µg of inhaled prostacyclin have been administered in humans with potent effects on pulmonary pressure and oxygenation. 89,90 Inhaled NO and prostacyclin may have additive actions as both medications act through different vasodilatory pathways. 91 Endothelin-1 is a potent vasoconstrictor released by endothelial cells in the pathophysiology of pulmonary hypertension.…”
Section: Rebound Pulmonary Hypertension and Hypoxemiamentioning
confidence: 99%